1983
DOI: 10.1029/jb088ib02p01129
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between surface topography, gravity anomalies, and temperature structure of convection

Abstract: Normal stresses associated with convection in a fluid layer, whose boundaries can deform, produce topography on those boundaries. When the equations of motion are linear, integral relations between topography on the boundaries and the temperature structure can be found as a function of wavelength. Expressions of this kind have been derived for the case of convection in a constant viscosity fluid when inertial effects are negligible. The total gravity anomaly is the sum of contributions due to the topography on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
195
2
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(204 citation statements)
references
References 28 publications
6
195
2
1
Order By: Relevance
“…[42] Several authors have demonstrated that the topography of the outer surface in mantle-like fluids is primarily controlled by the physical conditions within the uppermost thermal boundary layer [McKenzie, 1977;Parsons and Daly, 1983;Marquart and Schmeling, 1989]. Although ''dynamic'' loads associated with sublithospheric flow can influence the surface topography to some extent, this effect seems to be important only in regions of large upwellings or downwellings [e.g., Marquart and Schmeling, 1989].…”
Section: C1 Compensation Levelmentioning
confidence: 99%
“…[42] Several authors have demonstrated that the topography of the outer surface in mantle-like fluids is primarily controlled by the physical conditions within the uppermost thermal boundary layer [McKenzie, 1977;Parsons and Daly, 1983;Marquart and Schmeling, 1989]. Although ''dynamic'' loads associated with sublithospheric flow can influence the surface topography to some extent, this effect seems to be important only in regions of large upwellings or downwellings [e.g., Marquart and Schmeling, 1989].…”
Section: C1 Compensation Levelmentioning
confidence: 99%
“…In the convective mantle beneath the thermal lid, the effective depth of compensation may be limited by viscous stresses of convection that tend to balance thermal buoyancy forces [Parsons and Daly, 1983]. Studies of hotspot swells suggest compensation depths of 70 to 200 krn [e.g.…”
Section: White and Mckenziementioning
confidence: 99%
“…(2) ……… (3) Here, k | and z | represent non-dimensional wavenumber and depth of the convecting layer respectively. It is noticeable that model-2 produces higher amplitudes for theoretical admittance, and according to Parsons and Daly (1983) as the largest temperature variation occurs closer to the bottom boundary, the amplitude of transfer increases. The analytical expressions for the calculation of theoretical admittance curves for the above temperature distributions (after Parsons and Daly, 1983) and for different convective layer thicknesses (640 km and 400 km)…”
Section: Long Wavelength (> 800 Km) Geoid-bathymetry Admittancementioning
confidence: 99%
“…We compare the observed admittance values with the theoretical admittance curves computed for a simplified mantle convection model assuming Newtonian convection in a uniformly viscous mantle layer, and neglecting the effect of inertia, self-gravitation and sphericity (Parsons and Daly, 1983). It is known that the observed geoid can be defined as a function of the deformation of the upper and lower surfaces of the convective layer and density structure imposed by the temperature distribution (T) within the convective layer (Black and models 1 and 2.…”
Section: Long Wavelength (> 800 Km) Geoid-bathymetry Admittancementioning
confidence: 99%